Learning Progress in a Chinese Order of Stroke Game: The Effects of Intrinsic Cognitive Load and Gameplay Interest Mediated by Flow Experience. (July 2020) - Hong, Jon-Chao; Hwang, Ming-Yueh; Tai, Kai-Hsin; Lin, Pei-Hsin; Lin, Pei-Chun
When learning to write Chinese characters, it is essential for students to learn and maintain the correct order of the strokes. Chinese teachers often use computer-supported drill and practice to develop students' ability to write in the correct order, but such devices are rarely designed to stimulate learners' memory-manipulation in cognitive processes. To enhance the effect of the stimuli, a computer game called Chinese order of strokes was designed for students to practice their sensorimotor skill by providing a different color (i.e., red) to evoke learners' memory-manipulation cognitive processes. To understand the effect of this game, third-grade students from an elementary school in Taipei were invited to play Chinese order of strokes, and the correlates between their intrinsic cognitive load, gameplay interest, and flow experience were examined. The results showed that intrinsic cognitive load was negatively related to gameplay interest and flow, gameplay interest was positively related to flow, and flow was positively related to learning progress. The results imply that teachers can utilize a digital Chinese order of strokes to implement characters based on their own teaching materials and to facilitate the students' learning of the correct order of strokes.